Über eine Aufgabe vom Komplexepaar - Grincevičius, K. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: К. И. Гринцевичюс. Об одной задаче пар комплексов K. Grincevičius. Apie vieną kompleksų dvejetų uždavinį